Monitoring opportunistic behaviour, pressure behaviour and financial risk ratio between ASEAN countries / Muhammad Asyraff Mohd Yusoff - Mohd Yusoff, Muhammad Asyraff (Faculty of Business and Management, 2018)
This study is to examine the mean difference of earnings management. opportunistic behaviour, pressure behaviour and financial risk ratio between Asean countries namely Thailand, Malaysia and Indonesia, and also to find the relationship between opportunistic behaviour, pressure behaviour and financial risk ratio on earnings management. Based on the data gathered amounting 194 listed firms from Bursa Malaysia (Malaysia), Stock Exchange of Thailand (SET) and Indonesia Stock Exchange (IDX) for each country from the year Of 2014 to 2017. The study proposed that there will be a significant mean difference in earnings management, opportunistic behaviour, pressure behaviour and financial risk ratio between these three countries. Besides that, it is assumed that there will he significant relationship between opportunistic behaviour, pressure behaviour and financial risk ratio on earnings management. The result of this study enables the readers or regulators to have better explanation on the relationship between variables thus alter the rules and regulation a better and soundness of financial reporting in which will increase reliabilities.